PEMBUKTIAN TEOREMA HUKUM LEMAH BILANGAN BESAR DENGAN MENGGUNAKAN FUNGSI KARAKTERISTIK - Suci Sari Wahyuni; Dodi Devianto; Hazmira Yozza (Jurusan Matematika FMIPA Universitas Andalas Padang, 2013)
Let Xn be a sequence of random variables which have limited mean andvariance and also Sn = ni=1Xi, then the weak law of large number stated thatSn????E[Sn]n! 0 in probability, other variation of the weak law of large is; if Xn is asequence of random variables that distributed randomly and identically with mean inlimited variance, then Snn! in probability. Some papers proved the weak law by usinganalysis properties of random variable Sn. In this paper the law is is proved by usingcharacteristic function.